2001
DOI: 10.1002/1529-0131(200102)44:2<331::aid-anr50>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of power Doppler sonography with vascularity of the synovial tissue of the knee joint in patients with osteoarthritis and rheumatoid arthritis

Abstract: Objective. To examine the significance of power Doppler sonography (PDS) in the diagnosis of synovial hypertrophy of the knee joint by verifying and comparing the PDS findings with histopathologic findings of synovial membrane vascularity.Methods. The knee joints of 23 patients who were undergoing arthroplasty of the knee joint because of osteoarthritis or rheumatoid arthritis were examined with ultrasound before arthroplasty. The vascularity of the synovial membrane was classified semiquantitatively using PDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 24 publications
5
53
0
3
Order By: Relevance
“…Synovial hypertrophy in the superior and lateral recess was found in 59%, which is similar to the results by Walther et al ,22 who found 46% of patients with OA had hypertrophic synovial tissue by US examination.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Synovial hypertrophy in the superior and lateral recess was found in 59%, which is similar to the results by Walther et al ,22 who found 46% of patients with OA had hypertrophic synovial tissue by US examination.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies were not complete in regards to CE-MUS with PD and comparison with MRI: in some studies, the knee or finger joints rheumatoid arthritis patients were investigated without using MRI as a reference standard 1518 22. Another study used MRI in patients with knee OA without using PD or CE-MUS 23.…”
mentioning
confidence: 99%
“…Power Doppler or colour Doppler US is a valuable tool for assessing hyperaemia of synovial tissue. Doppler US findings correlate closely with histopathological findings of vascularity68 and also with arthroscopic vessel scores 69. No such studies have been published in gouty arthritis to date.…”
Section: Imagingsupporting
confidence: 55%
“…Ultrasonography scanning techniques, greyscale and power Doppler machine settings and definitions of abnormality were standardised among investigators prior to the study during a 1.5-day meeting. The US scanning method has been described previously 5 1822. Synovitis was defined according to the OMERACT published definitions 19 20 23 24.…”
Section: Methodsmentioning
confidence: 99%